Foreign exchange intervention: A new database - Marcel Fratzscher; Tobias Heidland; Lukas Menkhoff; Lucio Sarno; Maik Schmeling (Kiel Institute for the World Economy (IfW), 2020)
We construct a novel database of monthly foreign exchange interventions for 49 countries over up to 22 years. We build on a text classification approach that extracts information about interventions from news articles and calibrate our procedure to data about actual interventions. Our new dataset allows us to document stylized facts about the use of foreign exchange interventions for countries that neither publish their data nor make them available to researchers. Moreover, we show that foreign exchange interventions are used in a complementary way with capital controls and macroprudential regulation.
Keywords: F31; F33; E58; 330; foreign exchange intervention; capital controls; macroprudential regulation; international capital flows